Improved Approach for Modeling Nonlinear Site Response of Highly Strained Soils: Case Study of the Service Hall Array in Japan. Issue 2 (May 2016) - Motamed, Ramin; Stanton, Kevin; Almufti, Ibrahim; Ellison, Kirk; Willford, Michael
A nonlinear ground response analysis is conducted for the Niigata-ken Chuetsu-oki earthquake recorded at a free-field vertical array near the Kashiwazaki-Kariwa Nuclear Power Plant in Japan. A bidirectional site response analysis is carried out using LS-DYNA which allows user defined stress-strain relationships to dictate soil behavior subjected to dynamic loading. Dynamic soil behavior is characterized using a two-stage hyperbolic backbone curve implemented with modifications to consider the peak strength of soil layers as well as the strain at which the peak strength is fully mobilized. The effects of bidirectional input motions, strain rate, and the shape of the shear modulus degradation curves are investigated, and it is demonstrated that each factor can have a significant influence on the results.